Comprehensive analysis of m6A methylome alterations after azacytidine plus venetoclax treatment for acute myeloid leukemia by nanopore sequencing - Zaifeng Zhang; Lili Zhang; Jiangtao Li; Ru Feng; Chang Li; Ye Liu; Gaoyuan Sun; Fei Xiao; Chunli Zhang (Computational and Structural Biotechnology Journal, 2024)
N6 adenosine methylation (m6A), one of the most prevalent internal modifications on mammalian RNAs, regulates RNA transcription, stabilization, and splicing. Growing evidence has focused on the functional role of m6A regulators on acute myeloid leukemia (AML). However, the global m6A levels after azacytidine (AZA) plus venetoclax (VEN) treatment in AML patients remain unclear. In our present study, bone marrow (BM) sample pairs (including pre-treatment [AML] and post-treatment [complete remission (CR)] samples) were harvested from three AML patients who had achieved CR after AZA plus VEN treatment for Nanopore direct RNA sequencing. Notably, the amount of m6A sites and the m6A levels in CR BMs was significantly lower than those in the AML BMs. Such a significant reduction in the m6A levels was also detected in AZA-treated HL-60 cells. Thirteen genes with decreased m6A and expression levels were identified, among which three genes (HPRT1, SNRPC, and ANP32B) were closely related to the prognosis of AML. Finally, we speculated the mechanism via which m6A modifications affected the mRNA stability of these three genes. In conclusion, we illustrated for the first time the global landscape of m6A levels in AZA plus VEN treated AML (CR) patients and revealed that AZA had a significant demethylation effect at the RNA level in AML patients. In addition, we identified new biomarkers for AZA plus VEN-treated AML via Nanopore sequencing technology in RNA epigenetics.